2003
DOI: 10.1097/01.wcb.0000080703.47016.b6
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Beta Blocks Infiltration of Inflammatory Cells and Reduces Infarct Volume after Ischemic Stroke in the Rat

Abstract: The inflammatory response that exacerbates cerebral injury after ischemia is an attractive therapeutic target: it progresses over days and strongly contributes to worsening of the neurologic outcome. The authors show that, after transient ischemic injury to the rat brain, systemic application of interferon-beta (IFN-beta), a cytokine with antiinflammatory properties, attenuated the development of brain infarction. Serial magnetic resonance imaging (MRI) showed that IFN-beta treatment reduced lesion volume on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(97 citation statements)
references
References 48 publications
2
94
0
Order By: Relevance
“…In the CNS, both astrocytes and microglia express MMP9 (28), and it is also expressed by infiltrating macrophages (44). It has been shown that type I IFN inhibits MMP9 expression in astrocytes and microglia and reduces leukocyte infiltration to the CNS (29,43,(45)(46)(47). We find that in the absence of type I IFN signaling, MMP9 was significantly increased.…”
Section: Discussionmentioning
confidence: 49%
“…In the CNS, both astrocytes and microglia express MMP9 (28), and it is also expressed by infiltrating macrophages (44). It has been shown that type I IFN inhibits MMP9 expression in astrocytes and microglia and reduces leukocyte infiltration to the CNS (29,43,(45)(46)(47). We find that in the absence of type I IFN signaling, MMP9 was significantly increased.…”
Section: Discussionmentioning
confidence: 49%
“…IFNβ is an important downstream chemical product of TLR3 and TLR4 via TRIF. It has been shown that direct administration of IFNβ reduced ischemic brain damage in both rat and rabbit models of ischemic stroke [27][28][29] . The protective effects of IFNβ are associated with both preventing neutrophil infiltration and attenuating blood-brain barrier damage [28] .…”
Section: Discussionmentioning
confidence: 99%
“…Some macrophage and microglial response after injury is necessary for scavenging the necrotic debris facilitating plasticity (Danton and Dietrich, 2003). However, excess infiltration of leukocytes into the brain is detrimental and therapies that prevent leukocyte infiltration during the acute phase after ischemia are neuroprotective (Yrjanheikki et al, 1999;Veldhuis et al, 2003;Yenari et al, 2005;Garau et al, 2005). Individual inflammatory mediators play a complex role in promoting protection as well as destruction after brain injury.…”
Section: Discussionmentioning
confidence: 99%